Reframing Islamic Education through Contextualized Pedagogy: A Comparative Study of Indonesian and Saudi Secondary Schools - Khoirul Anam; Muzayyanah Sa’diyah; Ahmad Wara’; Ahmad Hafidz Lubis (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study examines how Islamic Religious Education is reframed through contextualized pedagogy in two different socio-cultural settings: SMAN 1 Pronojiwo in Indonesia and Al-Almas International High School in Hail, Saudi Arabia. Although previous studies have explored Islamic education and multicultural pedagogy, comparative research has yet to examine how contextual factors shape the enactment of Islamic values in educational practice. This study employed a qualitative comparative multiple-case study involving 18 participants, including teachers, school administrators, and students. Data were collected through semi-structured interviews, classroom observations, and document analysis, and were analyzed using reflexive thematic analysis. The findings reveal that contextualized pedagogy serves as a key mechanism linking Islamic teachings with students’ lived experiences. In Indonesia, pedagogical practices were grounded in community-based values and social interaction, while in Saudi Arabia, they were enacted through ethical reasoning, structured dialogue, and institutional guidance. Across both contexts, dialogical learning emerged as the primary process fostering multicultural citizenship, ethical awareness, and civic responsibility. The novelty of this study lies in proposing Contextualized Pedagogy as a conceptual framework explaining how socio-cultural realities and educational practices mediate Islamic values. The study contributes to Islamic educational theory and comparative education by highlighting the central role of pedagogy in shaping inclusive educational outcomes.